2007
DOI: 10.1002/ijc.22859
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with dendritic cells for prostate cancer

Abstract: Radical prostatectomy for prostate cancer is followed by PSA recurrence in up to 40% of patients. One third of patients with biochemical relapse progress to uncurable metastatic disease. Therefore, alternative treatment modalities are needed both in the situation of PSA recurrence and in hormone-refractory disease. Dendritic cells (DC) are the most powerful antigen-presenting cells, able to prime na€ ıve T-cells and to break peripheral tolerance and thus induce tumor immune responses. More than 400 prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 71 publications
1
21
0
6
Order By: Relevance
“…Similarly, most tumor immunotherapy approaches aim at enhancing the anticancer immune response but have had little success in human patients (3,4). One common reason for the inability of immune cells to eliminate cancers and the inefficiency of tumor immunotherapy is that malignant cells are immunoedited and selected to avoid elimination by the immune system (5).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, most tumor immunotherapy approaches aim at enhancing the anticancer immune response but have had little success in human patients (3,4). One common reason for the inability of immune cells to eliminate cancers and the inefficiency of tumor immunotherapy is that malignant cells are immunoedited and selected to avoid elimination by the immune system (5).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, this study has indicated that FcR-mediated phagocytosis of ICs enhances IL-12 p40 monomer/ homodimer secretion from DC, and a Ca2 + channel blocker, azelnidipine, has an additive effect on this enhancement. Until the present, cancer immunotherapy using tumour peptide-or antigen-loading of immature DCs ex vivo has resulted in some clinical responses, but most of them were transient and insufficient [49][50][51]. The use of a Ca2…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is no validated gold standard for immune monitoring in immunotherapy studies [46]. Delayed-type hypersensitivity, enzyme-linked immunosorbent spot, and tetramer analysis/T-cell proliferation have all been used as measurements of the immune response.…”
Section: Evaluation Of Immune-based Therapiesmentioning
confidence: 99%